IMPLEMENTASI MEDIA TECHNOLOGY ENHANCED EDUCATION DALAM MENINGKATKAN KEMAMPUAN BERPIKIR SPASIAL SISWA FASE F PADA MATERI KEANEKARAGAMAN HAYATI DI SMA NEGERI 1 BUKIT BATU - Aulia Laila Tamin; Yurni Suasti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of using technology-enhanced education media on improving students' spatial thinking skills at SMAN 1 Bukit Batu. The research method used in this study is a quasi-experimental method with a nonequivalent control group design. The research sample consisted of class XI.3 as the control class and class XI.4 as the experimental class, which were randomly selected. Data on spatial thinking were collected through tests and analyzed using a t-test. The results of the study found that there is an effect of technology-enhanced education learning media on the spatial thinking skills of students in class XI.3 at SMAN 1 Bukit Batu, with an average posttest score of 81.00 for the experimental class and 62.81 for the control class.